2004
DOI: 10.1097/01.hjh.0000133733.32125.09
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of indapamide SR and enalapril on microalbuminuria reduction in hypertensive patients with type 2 diabetes

Abstract: Indapamide-SR-based therapy is equivalent to enalapril-based therapy in reducing microalbuminuria with effective blood pressure reduction in patients with hypertension and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
18

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(75 citation statements)
references
References 37 publications
1
56
0
18
Order By: Relevance
“…34,40,[46][47][48][56][57][58][59] Clinical trials, grouped by the degree of albuminuria, demonstrating the beneficial effects of RAAS inhibition on renal end points in patients with diabetes mellitus are summarized in Table 2. 34,40,42,48,49,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Normoalbuminuria The Bergamo Nephrologic Diabetes Complications Trial (BENEDICT) is the only primary prevention study to date to demonstrate that the development of microalbuminuria can be prevented by the use of an ACE inhibitor alone or in combination with a CCB in hypertensive normoalbuminuric patients with type II diabetes. 59 …”
Section: Clinical Evidence Of Benefits Of Raas Inhibition In Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…34,40,[46][47][48][56][57][58][59] Clinical trials, grouped by the degree of albuminuria, demonstrating the beneficial effects of RAAS inhibition on renal end points in patients with diabetes mellitus are summarized in Table 2. 34,40,42,48,49,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Normoalbuminuria The Bergamo Nephrologic Diabetes Complications Trial (BENEDICT) is the only primary prevention study to date to demonstrate that the development of microalbuminuria can be prevented by the use of an ACE inhibitor alone or in combination with a CCB in hypertensive normoalbuminuric patients with type II diabetes. 59 …”
Section: Clinical Evidence Of Benefits Of Raas Inhibition In Patientsmentioning
confidence: 99%
“…70,71 Studies of diuretics (alone or in combination with an ACE inhibitor) suggest possible renoprotective benefits. 64,68 A low-dose combination of perindopril plus indapamide induced a greater decrease in UAER (À42%) than once-daily monotherapy with enalapril (À27%) in diabetic patients with hypertension and albuminuria. 68 This advantage remained after adjustment for the lower BP achieved by the combination group and for other factors.…”
Section: Multifaceted Approachesmentioning
confidence: 99%
“…The Natrilix SR versus enalapril study in hypertensive type 2 diabetics with microalbuminuria (NESTOR) set out to compare the effectiveness of two antihypertensive drugs: an ACEI, enalapril, and a diuretic, indapamide sustained release (SR) 12 with opposite effects on the reninangiotensin system (RAS) in reducing microalbuminuria. 13 Results of the study suggested that indapamide SR and enalapril reduced microalbuminuria to a similar extent, with equivalent mean BP control.…”
mentioning
confidence: 72%
“…An additional label treatment by amlodipine 5-10 mg (first step) and atenolol 50-100 mg (second step)/day was allowed after 6 weeks of treatment. 24 Results showed that the decrease in SBP was significantly (P ¼ 0.02) more important with indapamide SR (À23.8 mmHg) than with enalapril (À21.0 mmHg), Figure 2. The noninferiority of indapamide SR vs enalapril was achieved for microalbuminuria reduction.…”
Section: Sbp Lowering In Hypertensive Patients With Type II Diabetes-mentioning
confidence: 92%